Simple and robust monitoring of ethanol fermentations by capillary electrophoresis. (8th September 2014) - Oliver, James D.; Sutton, Adam T.; Karu, Naama; Phillips, Michael; Markham, Julie; Peiris, Paul; Hilder, Emily F.; Castignolles, Patrice
Abstract Free‐solution capillary electrophoresis (CE), or capillary zone electrophoresis, with direct UV detection was used for the first time for the determination of mono‐ and disaccharides, sugar alcohols, and ethanol in fermentation broths. Sample preparation proved to be minimal: no derivatization or specific sample purification was needed. The CE conditions can be adapted to the type of fermentation by simply altering the background electrolyte (BGE). KOH (130 mM) or NaOH (130 mM) as the BGE led to the fastest analysis time when monitoring simple fermentations. A mixture of 65 mM NaOH and 65 mM LiOH led to a 19% improvement in resolution for a complex mixture of carbohydrates. Quantification of a simple carbohydrate fermentation by CE showed values in close agreement with that of high‐performance anion exchange chromatography and high‐performance liquid chromatography (HPLC) on a cation exchange resin. For complex fermentations, quantification of carbohydrates by HPLC and CE led to similar results, whereas CE requires an injection volume of only 10–20 nL. Analysis of an ethanol fermentation of hydrolyzed plant fiber demonstrated the robustness of the separation and detection of carbohydrates, as well as ethanol. Ethanol determination is achieved by coupling the CE method to pressure mobilization, using the same instrument and the same sample.